Establishing and Validating a Model of Waste Heat Recovery System for Coal-fired Boilers based on a Spray Tower - Zhao Jinzi; Zhao Xiling; Wang Jingyi; Fu Lin; Sun Fangtian; Zhang Shigang (Zhileng xuebao)
Coal-fired boilers and thermal power plants are the primary heating resource in the district heating field. However, they have great energy-saving potential because of the significant heat loss from the high-temperature discharging flue gas. In view of the existing problems, a waste-heat recovery system for coal-fired boilers based on a spray tower is presented. It could efficiently recover the latent heat and improve the system efficiency and economic performance by using a spray-tower heat exchanger and absorption heat pump. In this study, a model was built for this system and validated with measured data in a practical project. The system was then evaluated from the points of view of energy saving, emission reduction, and economic feasibility. The results show that the simulation results of the model are roughly in line with the trend of the observed results, and the absolute and relative errors are in a reasonable range, which proves that the model is reasonable. Meanwhile, the boiler thermal efficiency can rise to 104.5%, the pollutant emissions can obviously decrease, and the quantity of collected condensate water can reach 18,000 tons a year. In addition, the payback period is 3.96 years. In summary, the proposed system has higher energy efficiency and better economic benefits than existing systems.